The natural world of the California Indians - Heizer, Robert F. 1915-1979 (Univ. of California Press, 1980)
Describes patterns of village life, and covers such subjects as Indian tools and artifacts, hunting techniques, and food.--From publisher description.
Keywords: Indianer; Indians of North America -- California